Implementasi Sistem Rujukan Terintegrasi (SISRUTE) di RSUD Labuang Baji Kota Makassar - Zahrawi Astrie Ahkam; Nurmiati Muchlis; Samsualam (Program Pascasarjana Universitas Muslim Indonesia, 2021)
Background: SISRUTE is the implementation of health services that regulates the transfer of duties and responsibilities of health services reciprocally, both vertically and horizontally, where the entire referral process is carried out in an integrated manner. SISRUTE is expected to be able to overcome delays in the patient handling process because adequate health service facilities are only in big cities and the a limited capacity of places to handle these patients. Method: The research method used in this research is a qualitative method and a phenomenological approach. Where this research was conducted in the interview stage to find out qualitative data in knowing the implementation of the integrated referral system (SISRUTE) at the Labuang Baji Hospital, Makassar City. Result: The results of this study found that the relationship between hospital variables and policy setting, the relationship between information variables and information recording and reporting, and the relationship between system variables and the use of hardware, software, and the expertise of Information Technology (IT) personnel in terms of definition. the system, human resource expertise, system appearance, features and functions, security, and access rights of informants rated it as well, while in terms of training, the use of the system and the constraints of using informants considered it bad. Conclusion: So it is recommended that Labuang Baji Hospital should provide more than one internet network, for example adding a modem, for referring hospitals and referral recipient hospitals to complete and update the database of resource availability, facilities, and blood banks, and integrate this data into SISRUTE.